Peranan Mulsa Dan Pembenah Tanah Pada Dinamika Dan Pengawetan Lengas Tanah - Santosa, AZ. Purwono Budi; Notohadisuwarno, Supriyanto; Soekodarmodjo, Soeprapto (Agriculture Faculty, University of Kutai Kartanegara, Indonesia, 2015)
A study of the soil moisture dynamics and conservation resulted from the mulch adding and soil amendment was carried out in the Laboratory of Soil Science of Agriculture Faculty of Gadjah Mada University. The experiment was conducted using a Factorial Completely Randomized Design consisting of mulch adding (Mo = without the mulch and M1 = with the mulch) and fourrates of soil amendment (Po = 0, P1 = 4, P2 = 8 and P3 = 12 Mg.ha-1). The experiment used Mediteran top soil ( Vertic Eutropepts ). Tensiometers were installed at the 15, 30 and 45 cm soil depths of all plots. Every treatment was repeated three times. The soil properties which were observed included particle size distributions, bulk density, particle density, soil moisture characteristic. Soil temperature, saturated and unsaturated hydraulic conductivity, organic matter, fulvic acid, C/N and HA/FA ratios. Tensoimeter readings were taken daily, diurnal variation in soil temperature at a depth of 15 cm and air temperature were monitored with thermometers. The result of this experiment, generally speaking, showed that the mulch adding decreases the upward flow of the soil moisture and reduces the evaporation rate and then decreases the loss of the soil moisture. The soil amendment from the green manure does not have a role to improve soil physical properties. However, it increases the ability to hold the soil moisture, so the loss of soil moisture resulted from percolation is decreased. In fact, the role of soil amendment to increase the soil moisture content is less than the mulch, and then there is no interaction between the two factors which are tested.Key Words : mulch, soil amendment, soil moisture dynamics, soil moisture conservation.